The dark matter of the cancer genome: aberrations in regulatory elements, untranslated regions, splice sites, non‐coding RNA and synonymous mutations. Issue 5 (18th March 2016) - Diederichs, Sven; Bartsch, Lorenz; Berkmann, Julia C; Fröse, Karin; Heitmann, Jana; Hoppe, Caroline; Iggena, Deetje; Jazmati, Danny; Karschnia, Philipp; Linsenmeier, Miriam; Maulhardt, Thomas; Möhrmann, Lino; et al.
Abstract: Cancer is a disease of the genome caused by oncogene activation and tumor suppressor gene inhibition. Deep sequencing studies including large consortia such as TCGA and ICGC identified numerous tumor‐specific mutations not only in protein‐coding sequences but also in non‐coding sequences. Although 98% of the genome is not translated into proteins, most studies have neglected the information hidden in this "dark matter" of the genome. Malignancy‐driving mutations can occur in all genetic elements outside the coding region, namely in enhancer, silencer, insulator, and promoter as well as in 5′‐UTR and 3′‐UTR. Intron or splice site mutations can alter the splicing pattern. Moreover, cancer genomes contain mutations within non‐coding RNA, such as microRNA, lncRNA, and lincRNA. A synonymous mutation changes the coding region in the DNA and RNA but not the protein sequence. Importantly, oncogenes such as TERT or miR‐21 as well as tumor suppressor genes such as TP53 / p53, APC, BRCA1, or RB1 can be affected by these alterations. In summary, coding‐independent mutations can affect gene regulation from transcription, splicing, mRNA stability to translation, and hence, this largely neglected area needs functional studies to elucidate the mechanisms underlying tumorigenesis. This review will focus on the important role and novel mechanisms of these non‐coding or allegedly silent mutations in tumorigenesis. Abstract : Coding‐independent mutations affect gene regulation from transcription, splicing, mRNA stability to translation. This one of a kind review discusses the largely neglected impact of this genome "dark matter" on tumorigenesis.